Australasian brachytherapy audit: Results of the 'end‐to‐end' dosimetry pilot study. Issue 4 (20th February 2013) - Haworth, Annette; Wilfert, Lisa; Butler, Duncan; Ebert, Martin A; Todd, Stephen; Bucci, Joseph; Duchesne, Gillian M; Joseph, David; Kron, Tomas
Abstract: Introduction: We present the results of a pilot study to test the feasibility of a brachytherapy dosimetry audit. Methods: The feasibility study was conducted at seven sites from four Australian states in both public and private centres. A purpose‐built cylindrical water phantom was imaged using the local imaging protocol and a treatment plan was generated to deliver 1 Gy to the central (1 of 3) thermoluminescent dosimeter (TLD) from six dwell positions. Results: All centres completed the audit, consisting of three consecutive irradiations, within a 2‐h time period, with the exception of one centre that uses a pulsed dose rate brachytherapy unit. All TLD results were within 4.5% of the predicted value, with the exception of one subset where the dwell position step size was incorrectly applied. Conclusions: While the limited data collected in the study demonstrated considerable heterogeneity in clinical practice, the study proved a brachytherapy dosimetry audit to be feasible. Future studies should include verification of source strength using a Standard Dosimetry Laboratory calibrated chamber, a phantom that more closely mimics the clinical situation, a more comprehensive review of safety and quality assurance (QA) procedures including source dwell time and position accuracy, and a review of patient treatment QA procedures such as applicator position verification.